2008
DOI: 10.1016/j.jmb.2008.05.015
|View full text |Cite
|
Sign up to set email alerts
|

Activation of the Escherichia coli marA/soxS/rob Regulon in Response to Transcriptional Activator Concentration

Abstract: SummaryThe paralogous transcriptional activators, MarA, SoxS and Rob, activate a common set of promoters, the marA/soxS/rob regulon of Escherichia coli, by binding a cognate site (marbox) upstream of each promoter. The extent of activation varies from one promoter to another and is only poorly correlated with the in vitro affinity of the activator for the specific marbox. Here, we examine the dependence of promoter activation on the level of activator in vivo by manipulating the steady-state concentrations of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

5
89
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 61 publications
(94 citation statements)
references
References 24 publications
5
89
0
Order By: Relevance
“…These data suggest an intracellular concentration-dependent response of the bacterium to increasing overexpression of ramA/RamA. We postulate that such a mechanism is dependent on transcriptional activator concentration and promoter sensitivity, similar to that established previously for E. coli marA, soxS, and rob (41). Our data further suggest that bacterial cells carefully "orchestrate" the level of RamA, with too much or none being deleterious to the bacterium.…”
Section: Discussionsupporting
confidence: 87%
“…These data suggest an intracellular concentration-dependent response of the bacterium to increasing overexpression of ramA/RamA. We postulate that such a mechanism is dependent on transcriptional activator concentration and promoter sensitivity, similar to that established previously for E. coli marA, soxS, and rob (41). Our data further suggest that bacterial cells carefully "orchestrate" the level of RamA, with too much or none being deleterious to the bacterium.…”
Section: Discussionsupporting
confidence: 87%
“…Interestingly, AraC subfamily members in E. coli often act as activators of stress responses (21). UirR binds to the promoter of the adjacent gene slr1214 that encodes the PatAfamily response regulator LsiR.…”
Section: Discussionmentioning
confidence: 99%
“…3) carrying the MarA wild type or mutant or the SoxS plasmid was reconstructed and purified immediately prior to assay. Since we have demonstrated that the MarA concentrations attained here (20) exceed the K m for the Lon protease, the levels of MarA in lon Ï© clpP Ï© cells are Ïł65% of those in lon clpP cells and should not affect the results significantly. Both M3997 and N8452 have null mutations in marRAB and rob to eliminate the basal levels of expression of the activators; the WT soxS present on the chromosome is negligibly expressed (our unpublished observations).…”
Section: Methodsmentioning
confidence: 57%
“…Table S1 in the supplemental material provides a list of the strains used in this study. The lacZ transcriptional fusions have been described previously (12,13,20,26,27) except for acrAB::lacZ. This fusion contains the acrAB promoter from nucleotides 485037 to 484920 fused to lacZ and was constructed as described previously (39); the transcription start site is at 484922 (11).…”
Section: Methodsmentioning
confidence: 99%